International migration : trends, policies and economic impact / edited by Slobodan Djaji c. - Djaji c, Slobodan (Routledge contemporary economic policy issues ;, 2001)
These essays provide a contemporary perspective on a broad range of international migration issues. They cover both trends and policies, examining links between migration and trade, economic growth, and the welfare state.